I Love Big Bird: How journalists tweeted humor during the 2012 presidential debates. Issue 2 (17th February 2016) - Mourão, Rachel; Diehl, Trevor; Vasudevan, Krishnan
Abstract : During the 2012 elections, several narratives built around humor, zingers, and gaffes blurred the lines between news and entertainment. This paper examines how political journalists used humor on Twitter during the first 2012 presidential election debate. This study also explores the character of such humor, how jokes relate to other forms of Twitter interactivity, and who, or what are the targets of these jokes. Twitter use by political reporters during a presidential debate might offer evidence of a deviation from traditional reporting norms. Recent scholarship on journalism practice and new media technologies suggests that journalists tend to "normalize" new media affordances; journalists often adapt long-standing routines to new technological platforms. Normalization offers a solid construct to guide inquiry on how social media might, or might not, affect change in the delivery and style of contemporary political news. A content analysis of tweets posted by 430 political journalists during the debate reveals widespread use of humor by journalists on Twitter, especially associated with the retweet function. About one-fifth of the journalists' tweets included jokes, suggesting a growing acceptance of the rhetorical device on Twitter. Results also reveal that journalists and commentators pointed their jokes toward political figures, but more sophisticated satirical comments were aimed at the news media or the debate process at large. Overall, political journalists tended to avoid humor as a means of criticism. Implications regarding the role of humor in politics, the nature of reporting on Twitter, and areas of potential future research are discussed.